Apakah Aspek Kewirausahaan Penting dalam Program Wakaf Tunai di Organisasi Islam Nahdlatul Ulama? - Ries Wulandari; Ismi Khumaedah (Universitas Islam Raden Rahmat, 2021)
Cash waqf is one of model of waqf. Cash waqf empowerment program GERWAKU SENA by Nahdlatul Ulama is one of many programs to support reducing poverty program in Indonesia. Due to its purpose this program must be supported by valuable research. The objectives in this research to find the main problem and the best solution to optimize Gerwaku Sena NU using ANP analysis. By using ANP Analysis, we composed the problem and solution in entrepreneur aspect into two groups namely internal and external. The research finding that the most influential problems on the waqf activity is lack of entrepreneur skill to solve operational cost problem and managerial aspect. In line with this problem, supporting entrepreneur skill for human resource is the key factor support the program.